Research on nanosecond time synchronization technology for 5G base station based on GNSS neighborhood similarity - Wenxue LIU; Shijun CHEN; Jian GE; Hong YUAN; Cuiling GONG (Tongxin xuebao)
For precision positioning requirements in the LTE-A/5G service developed by the 3GPP,the nanosecond precision time synchronization technology based on global navigation satellite system (GNSS) for 5G base station was studied which broke through the current GNSS receiver’s hundred nanosecond timing accuracy.By analyzing the characteristics of neighborhood similarity of GNSS errors and combining the characteristics of time synchronization requirements of 5G base stations,a nanosecond precision time synchronization theory and related receiver algorithms for 5G base stations was proposed which based on the principle of neighborhood similarity of GNSS signals.The specific characteristics of the time synchronization technology under regional and wide-area conditions were studied.The simulation and experimental results show that compared with the current time synchronization accuracy within hundred nanosecond rang of base stations,the proposed method can achieve precision time synchronization within 3 ns between the regional base stations,and support 5G base station meter-level precision location based service(LBS) and other advanced incremental services.